Structure-Antioxidant-Antiproliferative Activity Relationships of Natural C7 and C7-C8 Hydroxylated Flavones and Flavanones - Sandra Sordon; Jarosław Popłoński; Magdalena Milczarek; Martyna Stachowicz; Tomasz Tronina; Alicja Z. Kucharska; Joanna Wietrzyk; Ewa Huszcza (MDPI AG, 2019)
Common food flavonoids: chrysin, apigenin, luteolin, diosmetin, pinocembrin, naringenin, eriodictyol, hesperetin, and their analogues with an additional hydroxyl group at the C-8 position obtained via biotransformation were tested for antioxidant activity using the ABTS, DPPH, and ferric ion reducing antioxidant power (FRAP) methods. They were also tested for antiproliferative activity against selected human cancer cell lines—MV-4-11 (biphenotypic B myelomonocytic leukemia), MCF7 (breast carcinoma), LoVo (colon cancer), LoVo/DX (colon cancer doxorubicin resistant), and DU 145 (prostate cancer)—and two normal human cell lines—MCF 10A (breast cells) and HLMEC (lung microvascular endothelial cells). Flavonoids with a C7−C8 catechol moiety indicated much higher antioxidant activity compared with the C7 hydroxy analogues. However, because they were unstable under the assay conditions, they did not show antiproliferative activity or it was very low.